P82 Comparison of rsv hospitalisation in preterm infants with chronic lung disease who do not qualify for palivizumab prophylaxis with those who qualify in nottingham, uk. (15th November 2017) - Tsilika, L; Batra, D; Prayle, AP; Hurley, M; Bhatt, JM
Abstract : Introduction: Palivizumab prophylaxis reduces the likelihood of serious respiratory tract infection by Respiratory Syncytial Virus (RSV) in ex-preterm infants with Chronic Lung Disease (CLD). The Nottingham CLD service follows the Joint Committee on Vaccination and Immunisation (JCVI) guidelines for Palivizumab prophylaxis based on gestation, respiratory status and chronological age at the beginning of RSV season. This retrospective observational study was conducted to compare the RSV hospitalisations in preterm infants with CLD who are offered Palvizumab to those with milder CLD. Materials and Methods: We hypothesised that the RSV hospitalisation rate and length of hospital stay (LOS) within the 1 st year of life between preterm babies in home oxygen with CLD immunised according to the JCVI criteria and babies with moderate CLD not discharged in home oxygen would be comparable. Our cohort included babies born in Nottingham UK between 2009 and 2015. Data was collected from hospital records and the Nottingham CLD database, and analysed using Fisher's exact test for proportions and Mann-Whitney test for continuous data. Results: In total there were 3478 babies born preterm (<37 weeks GA) in Nottingham UK from 2009 to 2015. 245 babies had CLD at 36 weeks corrected GA. 192 of these babies were discharged in Home Oxygen and 135 of these babies were eligible for Palivizumab (JCVI). Conclusion: The RSV hospitalisation rate was lower in preterm infants who did not qualify for Palivizumab compared to infants who qualified according to JCVI guideline but this difference was not statistically significant. A large prospective multi-centre study is required to ascertain the clinical and economic benefits of including the wider group for Palivizumab prophylaxis.